Simvastatin enhanced antimicrobial effect of Ag+ against E. faecalis infection of dentine through PLGA co-delivery submicron particles. Issue 18 (1st September 2020) - Fan, Wei; Duan, Mengting; Sun, Qing; Fan, Bing
Abstract: Enterococcus faecalis (E. faecalis) is one of the dominant bacteria for refractory infections of teeth. Silver ions (Ag + ) have been proved to be a strong bactericide but with high cytotoxicity and discoloration property. Simvastatin is an agent used for dyslipidemia treatment and has anti-inflammatory property. In this study, Ag + and simvastatin were for the first time used in combination, and poly (lactide-co-glycolide) (PLGA) submicron particles carrying both Ag + and simvastatin (AgS-PLGA) were fabricated for further investigations. Results confirmed the enhanced antibacterial activity against E. faecalis of Ag + by simvastatin. AgS-PLGA could release both Ag + and simvastatin for 24 days and also showed enhanced antibacterial activities. On dentin slices, AgS-PLGA could enter dentinal tubules by ultrasonic activation and inhibit the colonization of E. faecalis . AgS-PLGA showed no cytotoxicity on MC3T3-E1 cells and slight suppressive effect on RAW-264.7 cells, and could reduce the secretion of IL-6 and IL-1β of RAW-264.7 cells. AgS-PLGA could be developed as a new biomaterial for infection and inflammation control for dental and related medical treatments.